RASIO LEGIS PENGATURAN BATAS MINIMAL USIA PERKAWINAN MENURUT UNDANG UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Rachmi Sulistyarini (Arena Hukum)
In its verdict, the Constitutional Court with the decision Number 22/PUU-XV/2017 ordered the legislators within a maximum period of 3 years since the decision to make changes to Law Number 1 of 1974 concerning Marriage. This paper analyses the legal ratio of regulating the marriage minimum age according to Law number 16 of 2019 concerning Amendments to Law 1 of 1974 concerning marriage. The purpose of this paper is to analyze the regulation legis ration of the minimum age for marriage according to Indonesian Marriage Law. This legal research uses a philosophical, legislation, and conceptual approach. The results shows that the legal ratio of regulating the minimum age for marriage according to Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage is the recognition of children’s rights, guarantees, protection and fair laws and equal treatment of the law so there is no discrimination.